Growth and Biomass of Three Important Energy Plantation Tree Species in Jharkhand State of India - Oraon, B. C.; Malik, M. S.; Bijalwan, Arvind; Dobriyal, Manmohan J. R. (Indian Forester, 2016)
Growth and biomass of three important energy plantation tree species viz. Acacia auriculiformis, Cassia siamea and Eucalyptus hybrid was studied in three districts (Deoghar in sub zone IV, Ranchi in sub zone V and East Singhbhum in sub zone VI) of agro climatic zone VII( Eastern plateau and hill region) of Jharkhand, India. The measurement was taken during 2011-12, when plantation reached at an age of four years. The comparison of growth performance in terms of survival per cent, plant height, diameter and total biomass of tree were done. Among three species, Eucalyptus hybrid was better as compared to other two species in terms of survival, growth and biomass. Survival per cent of all three species were found more than 75%. Growth performance (height and diameter) of Eucalyptus hybrid was found better as compared to other species. The tree height and diameter of Eucalyptus hybridÂ was recorded maximum 11.42m and 9.14cm followed by Acacia auriculiformis (5.54m and 4.69cm) and Cassia siamea (5.03m and 3.85cm). The data for fresh biomass of different above ground parts (bole, branches, leaves and barks) and below ground parts (roots) were also collected. The result indicated that Eucalyptus hybrid (average 307.69 kg/tree) had maximum fresh biomass as compared to other two species, whereas below ground maximum fresh biomass obtained by Acacia auriculiformis (average 19.33 kg/tree) followed by Cassia siamea (average 14.61 kg/tree) and the minimum fresh biomass of root obtained by Eucalyptus hybrid (13.45 kg/tree).